Pollen Morphology of some Thai Artabotrys R.Br. (Annonaceae) - Eiadthong, Wichan; Insura, Thawee (วารสารวนศาสตร์ไทย, 2022)
The pollen morphology of 15 Thai Artabotrys species were investigated under light microscope and scanning electron microscope. The result showed all Thai Artabotrys species are monad pollen, inaperture and apolar. The size of pollen grains are medium to large with range from 33.91 ± 0.41 to 55.90 ± 3.19 µm. The pollen shape classified based on P/E that were divided into 2 groups, subprolate and euprolate; 10 species having subprolate and 5 species having euprolate. The exine thickness have ranged from 1.84 ± 0.12 to 2.66 ± 0.16 µm. The exine ornamentations can be classified into 2 types; perforate-fossulate exine sculpture which having 13 species and rugulate sculpture which having 2 species. The palynological information could be used for species identification only 1 species, A. suaveolens which is subprolate shape and having rugulate exine sculpture, while the others are having perforate-fossulate exine sculpture. So, the pollen morphology of Artabortys species are useful as a supplement characters for taxonomic data. Keywords: Pollen morphology, Artabotrys, Thailand, Palynology